The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.7554/elife.78877
|View full text |Cite
|
Sign up to set email alerts
|

Disease-modifying effects of sodium selenate in a model of drug-resistant, temporal lobe epilepsy

Abstract: There are no pharmacological disease-modifying treatments that have an enduring effect to mitigate the seizures and comorbidities associated with established chronic temporal lobe epilepsy (TLE). Sodium selenate has been reported to have anti-epileptogenic effects if given before TLE onset. However, the majority of TLE patients already have established epilepsy when they present to the clinic. This study aimed to evaluate for disease modifying effects of sodium selenate treatment in the chronically epileptic r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 128 publications
0
16
1
Order By: Relevance
“…16 Animal studies have shown that shortened TL increases seizure frequency. 15,45 However, the results of these studies may not be consistent with the results of the MR studies for several reasons. Firstly, the two animal studies used different species and introduced seizures in an artificial way, making it difficult to extrapolate the findings to humans accurately.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…16 Animal studies have shown that shortened TL increases seizure frequency. 15,45 However, the results of these studies may not be consistent with the results of the MR studies for several reasons. Firstly, the two animal studies used different species and introduced seizures in an artificial way, making it difficult to extrapolate the findings to humans accurately.…”
Section: Discussionmentioning
confidence: 69%
“…Observational studies have shown that TL is shortened in patients with epilepsy 16 . Animal studies have shown that shortened TL increases seizure frequency 15,45 . However, the results of these studies may not be consistent with the results of the MR studies for several reasons.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There is strong evidence that repeated perturbation of liver circadian function can lead to metabolic disruption 48 and reports of altered systemic metabolic profiles in KASE rats, which persist even after ASM treatment. 25 There are some data suggesting lowered clock gene expression is associated with increased epileptogenesis 49 and some evidence indicating reduced clock gene rhythms in the pilocarpine-induced post-SE model of TLE. 50 Importantly, genetic deletion of the Bmal1 gene reduced the electrically induced seizure threshold in knockout mice compared with wild-type mice, suggesting that Bmal1 contributes to epileptic excitability.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, 11-week-old male Wistar rats (n = 40) underwent a modified low-dose KA intraperitoneal administration protocol. 24,25 Age-matched (sham, n = 40) controls were handled the same way during the same experimental session as the KASE rats did not receive KA but receive intraperitoneal saline injection (1 mL/ kg) instead. Following the initial injection of KA (7.5 mg/ kg ip), the rats were monitored for 45 min for behavioral seizures by an experimenter blinded to the drug administration (KA or saline) using the Racine scale.…”
Section: Key Pointsmentioning
confidence: 99%